Sporophyte Stage Genes Exhibit Stronger Selection Than Gametophyte Stage Genes in Haplodiplontic Giant Kelp - Molano, Gary; Diesel, Jose; Montecinos, Gabriel J.; Alberto, Filipe; Nuzhdin, Sergey V. (Frontiers in Marine Science, 2022)
Macrocystis pyrifera (giant kelp), a haplodiplontic brown macroalga that alternates between a macroscopic diploid (sporophyte) and a microscopic haploid (gametophyte) phase, provides an ideal system to investigate how ploidy background affects the evolutionary history of a gene. In M. pyrifera, the same genome is subjected to different selective pressures and environments as it alternates between haploid and diploid life stages. We assembled M. pyrifera gene models using available expression data and validated 8,292 genes models using the model alga Ectocarpus siliculosus. Differential expression analysis identified gene models expressed in either or both the haploid and diploid life stages while functional annotation identified processes enriched in each stage. Genes expressed preferentially or exclusively in the gametophyte stage were found to have higher nucleotide diversity (π = 2.3 × 10–3 and 2.8 × 10–3, respectively) than those for sporophytes (π = 1.1 × 10–3 and 1 × 10–3, respectively). While gametophyte-biased genes show faster sequence evolution, the sequence evolution exhibits less signatures of adaptations when compared to sporophyte-biased genes. Our findings contrast the standing masking hypothesis, which predicts higher standing genetic variation at the sporophyte stage, and support the strength of expression theory, which posits that genes expressed more strongly are expected to evolve slower. We argue that the sporophyte stage undergoes more stringent selection compared with the gametophyte stage, which carries a heavy genetic load associated with broadcast spawning. Furthermore, using whole-genome sequencing, we confirm the strong population structure in wild M. pyrifera populations previously established using microsatellite markers, and estimate population genetic parameters, such as pairwise genetic diversity and Tajima’s D, important for conservation and domestication of M. pyrifera.